Sr-BEARING PHOSPHATES OF THE APATITE SUPERGROUP FROM THE ALKALINE ROCKS OF THE KO - A.S. Osipov; A.A. Antonov; N.S. Vlasenko (Минералогия)
The paper presents a mineralogical description of Sr-bearing phosphates of the apatite supergroup found in eudialyte-aegirine-albite rocks of the Konder pluton, Khabarovsk krai. The Sr-dominant phases are associated with minerals of the lamprophyllite group and titanite, whereas the Ca-dominant phases are associated with calciocatapleite and kainosite-(Y), which are the products of the decomposition of eudialyte. The phosphates probably formed during post-magmatic alteration of host rock in a following sequence: stronadelphite → fluorostrophite → Sr-rich fluorapatite (fluorocaphite) → Na-REE-fluorapatite. Their variable chemical composition indicates decreasing Sr, Ba and F contents and increasing Ca, Na, REE and (OH) contents during crystallization. The crystallization sequence could reflect a decrease in alkalinity of the mineral-forming conditions.